2015
DOI: 10.1055/s-0034-1399424
|View full text |Cite
|
Sign up to set email alerts
|

Emphysema: Imaging for Endoscopic Lung Volume Reduction

Abstract: !Chronic obstructive pulmonary disease (COPD) is characterized by two entities, the more airway-predominant type ("bronchitis") on the one hand, and emphysema-predominant type on the other. Imaging via high-resolution computed tomography plays an important role in phenotyping COPD. For patients with advanced lung emphysema, new endoscopic lung volume reduction therapies (ELVR) have been developed. Proper selection of suitable patients requires thinsection reconstruction of volumetric CT image data sets also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Each endoscopic LVR technique differs in its mechanistic target and, therefore, safety and efficacy capability. Accordingly, each technique assesses different patient and disease characteristics, such as fissure integrity and collateral ventilation, to determine patient eligibility and LVR technique compatibility [1721]. Among these patient characteristics, disease heterogeneity is also assessed but, typically, is not evaluated within a lobe.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each endoscopic LVR technique differs in its mechanistic target and, therefore, safety and efficacy capability. Accordingly, each technique assesses different patient and disease characteristics, such as fissure integrity and collateral ventilation, to determine patient eligibility and LVR technique compatibility [1721]. Among these patient characteristics, disease heterogeneity is also assessed but, typically, is not evaluated within a lobe.…”
Section: Discussionmentioning
confidence: 99%
“…There are currently four endoscopic LVR techniques being investigated for patients with emphysema: valves, coils, sealants, and vapor [1721]. Due to intralobar collateral ventilation, valve LVR technologies are limited to a lobar approach where an entire lobe is targeted during an LVR procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Collateral ventilation prevents the valves from fully deflating the target area, thus limiting their effectiveness. Small studies have suggested that CT imaging may be sensitive, albeit not necessarily specific, for the detection of the interlobular fissures, and new automated techniques may improve its performance in this area, making it an important tool for the preprocedure planning of patients undergoing endobronchial lung volume reduction (68,69,78).…”
Section: Computed Tomographymentioning
confidence: 99%